Studi Literatur: Penurunan Intensitas Halusinasi Pendengaran dengan Terapi Musik pada Pasien Skizofrenia - Made Ambari Pramudia; I Gusti Ayu Diah Fridari (Jurnal Psikologi Perseptual)
Schizophrenia is a type of mental disorder characterized by deviations in the individual's thoughts, perceptions, emotions, movements, and behavior. Auditory hallucinations are one of the positive symptoms that between 60 and 80 percent of people with schizophrenia experience. Patients with auditory hallucinations might experience instructions to harm oneself or others, threats, insults, or mutually exclusive voices or sound. Music therapy is one form of therapy that can given. This study aims to examine and identify how the administration of nonpharmacological therapy in the form of music therapy can decrease the symptoms and signs of auditory hallucinations. The research method used literature review with the search terms “Music Therapy” and “Auditory Hallucinations” on the Garuda Portal and Google Scholar database. The outcomes of 10 studies showed that there was a gradual decrease in both their symptomps and signs of auditory hallucinations after schizophrenia patients received music therapy. Thus, it can be stated that music therapy can reduce the intensity of auditory hallucinations in schizophrenia patients, provide a feeling of relaxation, and make patients more comfortable.